Biodegradation of heavy oily sludge by a two-step inoculation composting process using synergistic effect of indigenous isolated bacteria. (April 2020) - Parhamfar, Maryam; Abtahi, Hamid; Godini, Kazem; Saeedi, Reza; Sartaj, Majid; Villaseñor, José; Coulon, Frederic; Kumar, Vinod; Soltanighias, Tayebeh; Ghaznavi-Rad, Ehsanollah; Koolivand, Ali
Graphical abstract: Highlights: The strains KA3 and KA4 were isolated from the heavy oily sludge. The strains were capable of degrading crude oil in the mineral-based medium. The two isolated strains exhibited the synergistic effect in oil biodegradation. About 90% of total petroleum hydrocarbons were removed in the composting system. Successful scaling-up was achieved from mineral-based medium to composting process. Abstract: The impact of two-step inoculation of indigenous strains and their synergistic effect in the scaling-up of petroleum hydrocarbons biodegradation from a mineral-based medium (MBM) to a two-phase composting process were investigated. After isolating the strains KA3 and KA4 from heavy oily sludge (HOS), their emulsification index (E24 ), bacterial adhesion to hydrocarbon (BATH), and oil degradation efficiency were evaluated in the MBM. Then, they were inoculated twice into the composting bioreactors lasted for the primary 8 weeks as the first phase (FP) and subsequent 8 weeks as the second phase (SP). The results indicated that the consortium of the two strains degraded 16-61% of crude oil (1-5% concentration) in the MBM. In the composting reactors, removals of 20 g kg −1 initial concentration of total petroleum hydrocarbons (TPH) were found to be 63.95, 61.00, and 89.35% for the strains KA3, KA4, and their consortium, respectively. The computed biodegradation constants indicated the synergistic effect of the two strains and the effectiveness of the second-step inoculation. The study demonstrated the successful scaling-up of HOS biodegradation from MBM to the two-phase composting process through two-step inoculation of the isolated strains.